1974
DOI: 10.1063/1.1663566
|View full text |Cite
|
Sign up to set email alerts
|

Photodetection by light-induced barrier modulation in Cu-diffused Au–CdS diodes

Abstract: Modified Schottky barriers of the type Au-CdS: Cu were prepared by diffusing Cu to a depth of O.l...{).2 JJ.m into single crystals of CdS, prior to evaporating rectifying Au contacts. The electronic and photoelectronic properties of these junctions are adequately described by a simple model in which the Cu acts as an ionized acceptor, resulting in a "humped" potential barrier between the Au and the bulk CdS. Hole trapping by the acceptors under band-gap illumination reduces their ionization and, consequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It should be highlighted that this light-induced barrier height modulation is much faster than the trap discharging or oxygen diffusion processes (which usually accounts for photodetectors with Ohmic contact). For example, previous studies showed that the photocurrent response time for Au-CdS and Pt-ZnO Schottky barriers were typically below 1 s. However, the time required for trap discharging or oxygen diffusion was usually on the order of several minutes or upto hours ,,, . Previously, Zhou et al reported that the reset time of ZnO NW photodetectors could be enhanced by intentionally deposited Schottky contact on single NW .…”
Section: Resultsmentioning
confidence: 99%
“…It should be highlighted that this light-induced barrier height modulation is much faster than the trap discharging or oxygen diffusion processes (which usually accounts for photodetectors with Ohmic contact). For example, previous studies showed that the photocurrent response time for Au-CdS and Pt-ZnO Schottky barriers were typically below 1 s. However, the time required for trap discharging or oxygen diffusion was usually on the order of several minutes or upto hours ,,, . Previously, Zhou et al reported that the reset time of ZnO NW photodetectors could be enhanced by intentionally deposited Schottky contact on single NW .…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical background.--Modified barrier heights due to shallow surface doping have been examined theoretically in considerable detail (9,(18)(19)(20)(21)(22)(23)(24)(25)(26) since the early 1970's. Various levels of approximation of carrier effects have been considered, including (i) the depletion approximation (9,(19)(20)(21)(22)(23)(24)(25), (ii) a limited inversion approximation that accounted for minority free-carriers outside the p* region (26), and (iii) numerical calculations, including both electron and hole free-carriers throughout the device structure (present work). In addition to approximations for the free-carrier densities, the effects associated with nonplanar doping profiles in the shallow p" layer have been considered by a number of authors (19,23).…”
Section: Discussionmentioning
confidence: 99%
“…Various levels of approximation of carrier effects have been considered, including (i) the depletion approximation (9,(19)(20)(21)(22)(23)(24)(25), (ii) a limited inversion approximation that accounted for minority free-carriers outside the p* region (26), and (iii) numerical calculations, including both electron and hole free-carriers throughout the device structure (present work). In addition to approximations for the free-carrier densities, the effects associated with nonplanar doping profiles in the shallow p" layer have been considered by a number of authors (19,23). A synopsis of these results pertinent to our data analysis follows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The light induced barrier height modulation is typically much faster than the oxygen diffusion process ͑on the order of several minutes or hours͒. For example, it was shown previously that the photocurrent response time for bulk Au-CdS Schottky barrier was typically below 1 s. 18 Very recently, it was also reported that the recovery time of ZnO NW UV-sensors could be improved by focus-ion-beam deposited contacts with Schottky barrier. 8 In this letter, we suggest that the response and recovery time can be enhanced by using NW networks with NW-NW barrier dominated conductance.…”
mentioning
confidence: 99%